Expert determination as an alternative dispute resolution: Perceptions of construction players in Malaysia / Nur Shamimi Abdul Wahab and Mohd Fisal Ishak - Abdul Wahab, Nur Shamimi; Ishak, Mohd Fisal (2020)
Disputes are inevitable elements in the construction industry that must be solved within a reasonable time. Expert Determination is one of the alternative dispute resolutions and it is already known in Malaysia. Although it has been proven that litigation and arbitration are time-consuming and costly, but the parties still preferred to choose the traditional resolution method compare to ADR due to the provisions provided in all standard forms of contract. In practice, the types of dispute that are referred to expert determination involve single issues and technical rather than legal questions. Hence, this research aims to identify the perceptions of construction players toward Expert Determination as an Alternative Dispute Resolution. The method used for this research was quantitative research. The respondents participated in this research are construction industry players consisting of contractors, developers, and consultants, which are architect, quantity surveyor and engineer in Klang Valley, Selangor. This research also used random sampling method with total of 380 construction industry players listed by number. 191 construction industry players were selected as according to Krejcie and Morgan to participate in this research by using random number generator and it is completely unbiased as the 380 industry players have an equal chance to be selected. Total of 191 questionnaires were distributed, but only 153 returned the questionnaire. All the data collected were analysed using descriptive statistics. The data received were interpreted using Statistical Packages for Social Science (SPSS) version 20.0.The results revealed that Expert Determination is a private and confidential procedure but it has limited opportunities for appeal once the decision has been made by an expert. While the perceptions from construction industry players towards Expert Determination are Expert Determination can prevent power imbalance in formal proceedings.